2009
DOI: 10.1007/s11187-009-9199-1
|View full text |Cite
|
Sign up to set email alerts
|

Who skims the cream of the Italian graduate crop? Wage employment versus self-employment

Abstract: Our data show a strong negative relation between academic achievement and self-employment status, i.e. we assess the skimming of the best graduates into wage and salary work. JEL -Classification: J24, J31

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Also, Wilson et al (2007, p. 402) highlight not only the importance of educational level but also the strong relationship between the inclusion of entrepreneurship education in tertiary education and entrepreneurial self-efficacy, indicating ''entrepreneurship education can be positioned as an equalizer, possibly reducing the limiting effects of low self-efficacy and ultimately increasing the chances for successful venture creation by women''. However, Castagnetti and Rosti (2011) suggested that the relationship between education and entrepreneurial activity may be contradictory because higher education might generate better outside options in paid employment, making the consideration of entrepreneurship as a desirable career option less probable. Given the different positions found in the literature, in this paper we consider the level of education to be an important factor for entrepreneurial activity.…”
Section: Educationmentioning
confidence: 99%
“…Also, Wilson et al (2007, p. 402) highlight not only the importance of educational level but also the strong relationship between the inclusion of entrepreneurship education in tertiary education and entrepreneurial self-efficacy, indicating ''entrepreneurship education can be positioned as an equalizer, possibly reducing the limiting effects of low self-efficacy and ultimately increasing the chances for successful venture creation by women''. However, Castagnetti and Rosti (2011) suggested that the relationship between education and entrepreneurial activity may be contradictory because higher education might generate better outside options in paid employment, making the consideration of entrepreneurship as a desirable career option less probable. Given the different positions found in the literature, in this paper we consider the level of education to be an important factor for entrepreneurial activity.…”
Section: Educationmentioning
confidence: 99%
“…According to Alm and Martinez‐Vazquez (), tax evasion is widespread in the transition economies because of underdeveloped tax legislation and complicated tax collection procedures. Finally, risk‐averse women also might prefer wage employment to self‐employment if employment protection legislation guarantees large benefits for young mothers employed in the salaried sector (see Castagnetti and Rosti, ) while the benefits are not available in the self‐employed sector. Since Ukraine has one of the most generous family policies in the world, with the mothers being eligible for 18 weeks of maternity leave and three years of parental leave, this factor reduces the likelihood that Ukrainian women will enter self‐employment.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, self-selection into employment is observed for females who tend to be more likely than males to stay out of the labour force. We are not aware of any study that uses a valid instrument to address the sample selection bias in the self-employment model, and the instruments utilized in the wage equations: number of children: see Castagnetti and Rosti, 2011;Fossen 2012; an interaction of having young children and marital status: see Mulligan and Rubinstein, 2008 are not applicable in our case because they violate the exclusion restriction. We follow other studies on the self-employment decision (see Ahn, 2010;Bernat et al, 2017;Kan and Tsai, 2006) and refrain from the selection correction.…”
Section: Hayduk and Williamsmentioning
confidence: 99%